The Shift of Legislative Power in Indonesia: A Review of the Legislative Function Within a Presidential System - Erham; Miftahuddin; Maskur (Journal of State Democracy, 2026)
This research examines the evolution of legislative power in Indonesia, shifting from an executive-heavy system to a legislative-heavy one post-1945 Constitutional amendments. Despite normative repositioning, contemporary practices reveal a paradoxical return to executive dominance, fueled by oversized coalitions and expedited legislative processes. This study uses a normative juridical method with statute, historical, and conceptual approaches to analyze this shift. Findings indicate that mechanisms such as the Omnibus Law and Perppu effectively marginalize checks and balances while reducing public participation to a mere formality. This phenomenon, categorized as autocratic legalism, reflects significant democratic backsliding where legal instruments are increasingly utilized for power consolidation rather than safeguard against authoritarianism. To restore constitutional balance, the study recommends institutionalizing political opposition, enhancing the DPR's independent technical capacity, and enforcing stricter judicial standards for meaningful public involvement. These measures are vital to ensuring legislative functions remain a true manifestation of popular sovereignty within modern democracy.